NK cell-mediated tumor cell killing by bispecific innate cell engagers induces ADCC-mediated activation of primary human dendritic cells - Heger, Lukas; Kaszubowski, Tomasz; Amon, Lukas; Lehmann, Christian; Wingert, Susanne; Medina-Echeverz, José; Koch, Joachim; Hackstein, Holger; Purbojo, Ariawan; Hartmann, Arndt; Alexiou, Christoph; Cesnjevar, Robert; et al. (OncoImmunology, 2026)
Bispecific antibodies are used for the treatment of hematological malignancies as well as solid tumors. One of their main effector mechanisms is the recruitment of effector cells such as CD8+ T cells and CD16A+ NK cells to tumor cells. Bispecific innate cell engagers (ICE®) harnessing CD16A+ NK cells have been shown to induce significant tumor cell lysis in preclinical models, translating to promising signs of clinical activity together with a well-managed safety profile. However, how killing of tumor cells by NK cells influences other innate immune cells in the tumor microenvironment, such as dendritic cells (DCs), instrumental in bridging innate and adaptive tumor immunity, is largely unknown. Thus, we here analyzed whether antibody-dependent cell-mediated cytotoxicity by NK cells affected human DC subpopulations. We could show that killing of tumor cells leads to a strong activation of human conventional DCs type 1 (cDC1), DC2, and DC3 with enhanced expression of co-stimulatory molecules as well as the secretion of proinflammatory cytokines. Further, DC subpopulations as well as surviving tumor cells showed increased expression of the immunoregulatory molecule PD-L1 that is known to dampen T-cell immunity. Nevertheless, ADCC boosted the capacity of cDC1 and DC2 to prime naïve T cell responses but not of DC3. Thus, our data suggests that the therapy with bispecific antibodies targeting NK cells may have the potential to facilitate adaptive antitumor immune responses via activation of cDC1 and DC
CRIS-Team Scopus Importer:2026-01-26
Keywords: Bispecific antibodies; m AFM; 24NK cell; CD16A; EGFR; dendritic cells; cDC1; DC2; DC3; ADCC